2011
DOI: 10.1111/j.1440-0960.2011.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor efficacy of oral tacrolimus in the treatment of severe generalized atopic eczema in adults: A small retrospective case series

Abstract: We report a small, but novel case series of four adults with severe generalized atopic eczema (AE) not responsive to several other immunomodulatory therapies, who were treated with oral tacrolimus (5 mg twice-daily). Three of the four patients failed therapy with systemic tacrolimus, despite two of these showing an initial clinical response; the fourth patient remains on tacrolimus monotherapy with good control of skin disease. Although oral tacrolimus was well-tolerated in this small group of adults, the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Besides case reports (374), one open-label study on a sequential treatment with oral (6 weeks) and topical tacrolimus (11 weeks) in 12 patients with severe AD resulted in a substantial reduction in pruritus (375). In contrast to these results, a case series in 4 patients with AD treated with 5 mg tacrolimus twice daily for 14 months showed poor results in 3 of the patients (376). Expert recommendation: We suggest cyclosporine, methotrexate and azathioprine for refractory CP associated with inflammatory dermatoses and CPG.…”
Section: Leukotriene Receptor Antagonists and Tnfαmentioning
confidence: 99%
“…Besides case reports (374), one open-label study on a sequential treatment with oral (6 weeks) and topical tacrolimus (11 weeks) in 12 patients with severe AD resulted in a substantial reduction in pruritus (375). In contrast to these results, a case series in 4 patients with AD treated with 5 mg tacrolimus twice daily for 14 months showed poor results in 3 of the patients (376). Expert recommendation: We suggest cyclosporine, methotrexate and azathioprine for refractory CP associated with inflammatory dermatoses and CPG.…”
Section: Leukotriene Receptor Antagonists and Tnfαmentioning
confidence: 99%
“…Side effects included nausea, vomiting and diarrhoea, and elevated serum creatinine in one patient. Other reports of its use in atopic dermatitis are limited to small case series …”
Section: Resultsmentioning
confidence: 99%
“…Other reports of its use in atopic dermatitis are limited to small case series. 54,55 Intravenous immunoglobulin (IVIG) and intramuscular immunoglobulin Intravenous immunoglobulin, a plasma product pooled from up to 20 000 donors, has been assessed in a randomised placebo-controlled study in 40 children with moderate-to-severe atopic dermatitis; significant improvement was noted after 3 doses of IVIG (2 g/kg/month). 56 In another study of 10 children refractory to systemic immunosuppression, monthly treatment for 2 years was associated with significant symptomatic improvement, fewer infection-related exacerbations, a decrease in IgE, and being able to stop immunosuppressants in five cases.…”
Section: Oral Tacrolimusmentioning
confidence: 99%
“…Two studies have earlier been reported (1, 2) of oral tacrolimus treatment in atopic dermatitis. A case series of 4 patients using 5 mg twice-daily for up to 14 months showed poor effect in 3 of the patients (2). An openlabel study with 12 patients used, first, oral tacrolimus for 3 weeks, subsequently both oral and topical tacrolimus for 3 weeks, and finally topical tacrolimus alone for 8 weeks (1).…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus is widely used topically to treat skin diseases, particularly atopic dermatitis. A few studies have explored the use of oral tacrolimus in inflammatory skin diseases, such as atopic dermatitis and psoriasis (1)(2)(3).…”
Section: Short Communicationmentioning
confidence: 99%